GE_GERICHTE C/7384/2017 vom 14. Januar 2020 - GE Cour de justice (2020)
ACCIDENT DE LA CIRCULATION;LÉGITIMATION ACTIVE ET PASSIVE;DOMMAGE EFFECTIF | LCR.58.al1; LCR.62.al1; LCR.65.al1; CO.41.al1; CO.42.al1; CO.42.al2; CC.930; CC.931